Hubungan Kualitas Tidur dengan Kualitas Hidup Lansia Penderita Hipertensi di Wilayah Kerja Puskesmas Sidomulyo - Harfika Harfika; Ulfatul Muflihah; Siti Khoiroh Muflihatin (SEHATI: Jurnal Kesehatan, 2026)
One of the factors contributing to a decline in the quality of life among elderly individuals with hypertension is sleep quality. Sleep disturbances, such as insomnia or non-restorative sleep, can affect blood pressure regulation. Poor sleep quality, including short sleep duration, may trigger activation of the sympathetic nervous system and increased cortisol levels, which directly impact blood pressure. Elderly patients with hypertension commonly experience poor sleep quality, characterized by reduced sleep efficiency and frequent nocturnal awakenings. This study aimed to determine the relationship between sleep quality and quality of life among elderly patients with hypertension in the working area of the Sidomulyo Public Health Center. This study employed a quantitative research design using a descriptive correlational method with a cross-sectional approach. A total of 210 respondents were included in the study. Bivariate analysis was performed using the chi-square test. Statistical analysis revealed a p-value of 0.001 (0.05), indicating a very significant relationship between sleep quality and quality of life. A significant relationship exists between sleep quality and quality of life among elderly patients with hypertension in the working area of the Sidomulyo Public Health Center